2021
DOI: 10.1021/acs.energyfuels.0c04045
|View full text |Cite
|
Sign up to set email alerts
|

Chelating Agents as Acid-Fracturing Fluids: Experimental and Modeling Studies

Abstract: Acid-fracturing operations are applied to improve the productivity of carbonate reservoirs by creating rough fracture surfaces that remain conductive for reservoir fluids after the fracture closure. Different acid types have been used over the history of acid fracturing, including weak organic and strong HCl acids. Organic acids have low dissolving power, generating low fracture conductivity, while HCl acid is corrosive and requires numerous additives. For the first time, this study investigates the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 56 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, others investigated the effect of acid treatment on the mechanical rock structure (Zhang et al 2020b) and the influence of the rock mineralogy on acidizing efficiency (Martyushev et al 2022). Various acidizing fluids such as self-diverting acid (Bazin et al 1999;Lungwitz et al 2007), visco-elastic surfactant (VES) acid, gelled acid, self-generated acids, and recently, emulsified acid (Martyushev and Vinogradov 2021) and chelating agents (Tariq et al 2021) have been developed and investigated both in the laboratory and in field-scale (Gou et al 2021;Hassan and Al-Hashim 2017;Isah et al 2021a, b;Kiani et al 2021;Lai et al 2021;Li and Shi 2021;Martyushev and Vinogradov 2021;Melendez et al 2007;Taylor and Nasr-El-Din 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, others investigated the effect of acid treatment on the mechanical rock structure (Zhang et al 2020b) and the influence of the rock mineralogy on acidizing efficiency (Martyushev et al 2022). Various acidizing fluids such as self-diverting acid (Bazin et al 1999;Lungwitz et al 2007), visco-elastic surfactant (VES) acid, gelled acid, self-generated acids, and recently, emulsified acid (Martyushev and Vinogradov 2021) and chelating agents (Tariq et al 2021) have been developed and investigated both in the laboratory and in field-scale (Gou et al 2021;Hassan and Al-Hashim 2017;Isah et al 2021a, b;Kiani et al 2021;Lai et al 2021;Li and Shi 2021;Martyushev and Vinogradov 2021;Melendez et al 2007;Taylor and Nasr-El-Din 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Through core-flooding experiments, Barri et al [ 51 ] found that DTPA can create wormholes in the carbonate reservoir rocks. Recently in our previous study [ 52 ], we found that chelating agents can improve the fracture conductivity by many folds because of the rock dissolution. Based on previous experiences, DTPA and GLDA were used to dissolve filter cake.…”
Section: Methodsmentioning
confidence: 99%
“…Several experiments/measurements were performed, the lab-scale outcomes were reproduced numerically, and field-scale simulations were carried out. 30 …”
Section: Introductionmentioning
confidence: 99%